HR practice in garments industry: a case study on ABA Group Bangladesh - Islam, Mohd Aminul; Hossin, M.M. Ismail; Hoque, M.A.K. Fozlul (LAP Lambert Academic Publishing, 2017)
This book consist of several chapters where we details describe about Human Resource Management in a very well-known Garment company in Bangladesh. We really found a very fruitful information through this study. However there are a lot of gaps in a managerial skills and to trainer who really do not have enough knowledge to develop their employee. We have found it very recently and it was a first time case study among garments industries in Bangladesh. Hope you will find this book as a informative text book for your future research and development in your organization and your institution as well. Thank you